Pemanfaatan Botol Bekas Sebagai Media Penyiraman Secara Otomatis Pada Tanaman Sayuran - Dita Safira; Fadiyah Aprilia; Anisa Gustia Ningsih; Fatimah Fatimah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to explain the use of used bottles as a medium for automatic plant watering. In addition, this study also provides education to the community so that they can use used bottles at home as a medium for automatic plant watering. This activity also has a positive impact on environmental sustainability. This study uses the Classroom Action Research (CAR) research method. The results of this study are that the people of Mekar Baru village, Sei Balai sub-district, Batubara Regency are interested and show high interest in the use of used bottles as a medium for automatic watering of vegetable plants. The results of the activity can also maintain environmental sustainability by not littering.